Optimizing the Boosting Schedule of Subunit Vaccines Consisting of BCG and “Non-BCG” Antigens to Induce Long-Term Immune Memory - Lv, Wei; He, Pu; Ma, Yanlin; Tan, Daquan; Li, Fei; Xie, Tao; Han, Jiangyuan; Wang, Juan; Mi, Youjun; Niu, Hongxia; Zhu, Bingdong (Frontiers in Immunology, 2022)
Boosting Bacillus Calmette-Guérin (BCG) with subunit vaccine is expected to induce long-term protection against tuberculosis (TB). However, it is urgently needed to optimize the boosting schedule of subunit vaccines, which consists of antigens from or not from BCG, to induce long-term immune memory. To address it two subunit vaccines, Mtb10.4-HspX (MH) consisting of BCG antigens and ESAT6-CFP10 (EC) consisting of antigens from the region of difference (RD) of Mycobacterium tuberculosis (M. tuberculosis), were applied to immunize BCG-primed C57BL/6 mice twice or thrice with different intervals, respectively. The long-term antigen-specific immune responses and protective efficacy against M. tuberculosis H37Ra were determined. The results showed that following BCG priming, MH boosting twice at 12-24 weeks or EC immunizations thrice at 12-16-24 weeks enhanced the number and function of long-lived memory T cells with improved protection against H37Ra, while MH boosting thrice at 12-16-24 weeks or twice at 8-14 weeks and EC immunizations twice at 12-24 weeks or thrice at 8-10-14 weeks didn’t induce long-term immunity. It suggests that following BCG priming, both BCG antigens MH boosting twice and “non-BCG” antigens EC immunizations thrice at suitable intervals induce long-lived memory T cell-mediated immunity.